G14(P) Understanding young people with diabetes: using experience based co-design to provide a patient-centred diabetes transition service. (12th March 2018) - Soni, A; Freeman, E
Abstract : Aim: To use experience based co-design to improve the Diabetes Transition Service. Design: Young people with diabetes (type 1 and 2) managed by a district general Paediatric Diabetes Team, were invited to attend a focus group. The focus group, held in a local café, afterschool, was facilitated by 2 members of the Paediatric Diabetes team and the Diabetes Psychologist. A graphic designer attended to support the young people to visually explore and communicate their experiences and ideas. Results: 5 young people attended the group, ages 15–17 years. Each attendee was invited to tell their diabetes story, followed by facilitated individual and group discussions about the transition service and health and social wellbeing of young people in relation to diabetes. Recurrent themes that emerged included: promotion of independence, consistency of care, access to information and support via email and the internet, and the desire for peer-support opportunities. Changes in administration at the time of transition was highlighted to promote self-advocacy. The attendees strongly preferred physicians to be direct in their communication styles and to be seen individually by each member of the diabetes multidisciplinary team. They emphasised the need for after-school appointments and agreed that the hospital was a convenient location. The attendees were all keen on receiving information about diabetes and driving, alcohol, drugs, exam stress, contraception and pregnancy, some indicating a preference for written information (leaflets/website links) and others face to face discussions. All attendees identified a strong desire for the team to facilitate email contact and social events with others transitioning and those who have transitioned. 100% of the young people said that they would attend another focus group. Conclusion: This focus group wants a diabetes transition service that promotes self-advocacy and independence, allows them to see the same consultant who communicates openly and directly, have access to information about how diabetes affects issues facing young people, and a service that provides them with ongoing peer-support. Experience based co-design can ensure that diabetes transition services provide young people with a patient-centred service, that promotes ongoing health and social wellbeing well in to adulthood.